The Sipakatau dalam Masyarakat Bugis Bone Perspektif Al-Qur’an - BAKRI, SUBHAN (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
As the times and advances in human civilization, the noble values ​​of culture began to be forgotten by the current generation. Sipakatau culture has become one of the cultures that is almost forgotten by Bugis humans. The term sipakatau which means